THE EFFECT OF SOCIAL MEDIA MARKETING AND BRAND CREDITABILITY TOWARD PURCHASE INTENTION USING MODERATING CUSTOMER ATTITUDE IN INDONESIAN CONSUMERS OF GOJEK ONLINE PUBLIC TRANSPORTATION SYSTEM - Grace Citra Dewi; Gladys Greselda Gosal; Teofilus Teofilus; Sutanto Hidayat; Bambang Sugiyono Agus Purwono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Social media marketing has turned into a significant part of digital marketing techniques for brands and organizations. Utilizing the force of social media necessitates that you keep awake to date with its steadily changing landscape. “Gojek” (Online-public transportation sytem), a popular ride hailing platform in Indonesia, which uses social media marketing techniques to stay competitive in the market. in particular, discussed the impacts of social media influencer marketing and brand credibility toward purchase intention of Gojek services with the mediating role of customer attitude. The purpose of this research are: 1) to analyze the effects of social media influencer marketing towards customer attitude. 2) to analyze the effects of brand credibility towards customer attitude. 3) to analyze the effects of customer attitude towards purchase intention. This research design uses a Quantitative approach and are used to study certain populations and samples. Research variables are Social Media Influencer Marketing, Brand Credibility, Customer Attitude, and Purchase Intention. Number of respondent is 75 male and 76 female. The research results are Gojek had many great social media influencers, to increase their customer attitude, Gojek can create more social media influencers by focusing on the influencer’s popularity based on the questionnaire result, Brand credibility has a positive effect toward customer attitude, and Customer attitude has a positive effect toward purchase intention.